(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
The objective of this study was to clarify the inside of socio-economic condition and cattle production scenario in few areas of Pabna district. Data of socio-economic condition of farmers, cattle population, genotype and overall management were collected from three villages at Bera upazila of Pabna district during August to September in 2017. The collected data were tabulated and analyzed following one-way ANOVA including descriptive statistics. It was observed that the age of farmers were average 42 years with 19 years of average farming experiences. Agriculture was found as primary occupation (47.37%) followed by house wife (15.79%) and animal husbandry (10.53%). Among the total livestock population, 52% (n=286) was cattle with different genotypes but the frequency of local Pabna cattle was highest (70%). About 79% cattle were reared intensively at home because the areas were surrounded by water. The average peak day milk yield (4.56 liters) of local Pabna cattle was significantly (p <0.001) lower than Holstein crossbred (7.43 liters). The cattle feeding system was mostly intensive (77%) followed by semi-extensive (23%) with 60%, 49% and 98% restricted feeding for straw, green grass and concentrate feeds in the studied households. The capacity building training of farmers including different farm oriented facilities would enhance a dairy development programme in those areas from local Pabna cattle which could contribute their socio-economic condition as well. Res. Agric. Livest. Fish.4(3): 181-185, December 2017